Temporal analysis of elite men's doubles beach tennis matches - Lima, G. R.; Carminatti, L. J.; Turnes, T. (International Journal of Sports Science & Coaching, 2025)
Beach tennis (BT) is a fast-paced racket sport played by two teams of two players on a sand court. Despite its growing popularity, limited data exist on match dynamics, especially regarding active play duration and work-to-rest ratios in high-level BT. This study aimed to describe the temporal characteristics and work-to-rest ratios of elite men's doubles BT matches. Official videos of all finals from the World Championship and Sand Series during the 2022/2023 season of the professional World BT Tour were analyzed. Metrics recorded included match, set, game, and point durations, work-to-rest ratios, points per match, touches per point, and game speed. Seven final matches with ten elite players were analyzed. Matches lasted 1 h 16 min 41.71 s ± 12 min 30.05 s, with only 06 min 32.55 s ± 1 min 12.26 s (8.6%) spent in active play. The work-to-rest ratio ranged from 1:8 to 1:12. Each match had 106 ± 10 points, with 4.6 ± 0.5 touches per point, and points were completed in 3.65 ± 0.5 s, averaging one touch every 0.79 ± 0.04 s. Elite men's BT is characterized by short, high-intensity points with a work-to-rest ratio of 1:8 to 1:12, which has implications for training strategies focused on bursts of high-intensity efforts and recovery periods.